Students Incubator Business: A Mentorship Program for Creating Promotional Media for Student Micro Businesses Using Canva - Karina, Anggita Ajeng; Erinda, Hayyu; Wijaya, Dandi Nurmansyah; Nikma, Irfianinza Risqulia; Yuliono, Gun; Ulum, Miftahul; Widayanti, Erma; Christianto, Yudhi (Letters in Information Technology Education (LITE), 2024)
The "Students Incubator Business" program at SMAN 8 Malang aims to enhance students' skills in managing micro businesses by creating effective promotional media using Canva. The program comprises several stages: participant registration, workshops, mentoring, project assessment, and evaluation. A total of 20 students with micro businesses participated in this program, which involved intensive training in graphic design and digital marketing. The results showed increased students' knowledge and skills, mainly using Canva to create attractive promotional media tailored to their target markets. Program evaluation indicated that 80% of participants successfully produced high-quality promotional media, while the rewards effectively boosted students' motivation and confidence. Despite the program's success, ongoing mentorship is needed, particularly in copywriting strategies, to enhance marketing effectiveness further. Overall, this program successfully supported students in developing their micro businesses by improving their digital marketing skills.